A poly(hydrogen fluoride ethylene propylene) hollow fiber microporous membrane for edible oil filtration and a preparation method thereof

CN122806333APending Publication Date: 2026-09-25山东海化美天膜材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611277533.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

目前可用于食用油过滤的聚合物膜材料主要包括聚丙烯、聚偏氟乙烯、聚四氟乙烯等,但均存在明显的应用局限性:聚丙烯膜耐热性差,在食用油热滤工况下易发生热变形;聚偏氟乙烯膜长期接触非极性油品易发生溶胀,导致截留性能失效;聚四氟乙烯膜虽耐温耐腐性能优异,但成膜工艺受限,孔径可控性差,难以稳定实现高精度过滤,且工业化生产成本较高

Benefits of technology

1.本申请采用本体成孔路线,无需外覆聚酰亚胺分离涂层即可实现有效过滤,解决了外源涂层在高温非极性油品中易溶胀、剥离的寿命痛点,同时避免了涂层制备过程中有毒有机溶剂与交联剂的残留风险,食品接触安全性与长期工况稳定性显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122806333A_ABST
    Figure CN122806333A_ABST
Patent Text Reader

Abstract

The application discloses a kind of polyperfluoroethylene propylene hollow fiber microporous membrane for edible oil filtration and its preparation method, belong to polymer separation membrane technical field.The microporous membrane is prepared from 63-72% polyperfluoroethylene propylene resin, 22-29% water-soluble composite pore-forming agent and 2-5% fluorine-containing modified polyimide microfiber by mass percentage;Wherein the molar content of hexafluoropropylene structural unit of polyperfluoroethylene propylene resin is 11-14%, and the water-soluble composite pore-forming agent is prepared by wet compounding, fractional drying of inorganic salt component and polymer dispersion component.The present application does not need exogenous coating layer, can construct gradient pore structure in situ, has high retention precision, high permeation flux and excellent thermal stability, adapts to high-temperature precision filtration working condition of edible oil, and has strong controllability, easy industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a perfluoroethylene propylene hollow fiber microporous membrane for edible oil filtration and its preparation method, belonging to the field of membrane separation technology. Background Technology

[0002] The degree of refining of edible vegetable oils directly determines their quality and storage stability. Residual gums, waxes, fine mechanical impurities, and pigment aggregates in finished oils not only affect their transparency and flavor but also shorten shelf life and pose potential food safety risks. With the development of the high-end edible oil industry, the industry's requirements for filtration precision are continuously increasing. Some high-end products now require effective retention of submicron particles, placing higher demands on the precision, stability, and food safety compliance of filtration technology. Traditional edible oil filtration methods, such as plate and frame filtration, diatomaceous earth filtration, and filter paper filtration, generally suffer from limitations such as limited filtration precision, high material consumption, susceptibility to secondary contamination, and inability to operate continuously, making it difficult to meet the precision filtration needs of high-end edible oils.

[0003] Membrane separation technology is a novel and efficient separation technology with advantages such as energy saving, environmental friendliness, and resource reuse. Currently, polymer membrane materials that can be used for edible oil filtration mainly include polypropylene, polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE), but all of them have obvious application limitations: polypropylene membranes have poor heat resistance and are prone to thermal deformation under the conditions of hot filtration of edible oils; PVDF membranes are prone to swelling when in contact with non-polar oils for a long time, leading to failure of retention performance; although PTFE membranes have excellent temperature and corrosion resistance, the film formation process is limited, the pore size controllability is poor, it is difficult to stably achieve high-precision filtration, and the industrial production cost is high.

[0004] Perfluoroethylene propylene (FEP) is a copolymer of tetrafluoroethylene (TFE) and hexafluoropropylene (HFP). It has a fully fluorinated molecular structure, which not only has excellent chemical and thermal stability, but also good melt processing properties.

[0005] Currently, research on FEP hollow fiber membranes, both domestically and internationally, mainly focuses on general separation applications such as industrial wastewater treatment and organic solvent purification. There are existing reports on the preparation of FEP hollow fiber membranes. Conventionally, FEP is used as the film-forming polymer, composite inorganic particles as the pore-forming agent, and dioctyl phthalate (DOP) as the diluent, and FEP hollow fiber membranes are prepared via melt spinning. Some studies have also used MT-II type composite powder as the pore-forming agent and employed a melt spinning and stretching method to prepare FEP hollow fiber membranes. Furthermore, there are techniques that use FEP resin, a water-soluble compound pore-forming agent, and a polyimide modifier to form a multi-component spinning system, and then prepare FEP hollow fiber membranes via melt spinning and stretching. Chinese invention patent application CN115337796 A discloses a poly(fluoroethylene propylene)-based hollow fiber membrane. It uses FEP resin, a compounded pore-forming agent, and a polyimide modifier to prepare a nascent base membrane. A polyimide separation layer is then coated onto the base membrane surface using a concentric circular composite spinning process, achieving high-precision filtration through this nanoscale surface separation layer. However, this type of composite coating solution has a high dependence on organic solvents, making it difficult to meet the safety requirements of food contact scenarios such as edible oil filtration. Furthermore, under long-term high-temperature filtration and repeated backwashing conditions, the coating is prone to swelling, aging, and even interfacial peeling, resulting in rapid degradation of membrane performance.

[0006] When the inventors attempted to directly apply existing general-purpose FEP hollow fiber membranes to edible oil filtration, they discovered several problems: 1. Existing preparation processes mostly use organic solvents and cross-linking agents, which pose a risk of small molecule residues and cannot meet the safety requirements for food contact materials; 2. The membrane surface is not well-suited to non-polar oils, resulting in rapid flux decay during filtration. Colloidal impurities are prone to causing irreversible contamination, making cleaning and regeneration difficult. Furthermore, it is difficult to consistently and effectively retain submicron and micron-sized particles, colloidal aggregates, and waxy particles in terms of the cleanliness of the filtered oil, making it difficult to achieve an industrial balance between filtration accuracy and production flux. 3. Under long-term high-temperature oil immersion conditions, the stability of the membrane structure and retention performance is insufficient, making it difficult to meet the lifespan requirements for continuous industrial operation.

[0007] Based on this, this application is hereby submitted. Summary of the Invention

[0008] To address the aforementioned issues, this invention provides a perfluoroethylene propylene hollow fiber microporous membrane for edible oil filtration and its preparation method. This invention utilizes bulk pore formation combined with wet composite pore formation, optimizes raw material components, and incorporates differential cooling melt spinning, staged solid-phase stretching, and gradient water washing depore-removing processes to produce a hollow fiber microporous membrane with controllable porosity, high axial strength, and stable hot oil flux. Without relying on external separation coatings, it achieves a synergistic improvement in filtration accuracy, permeation flux, thermal stability, and food safety, making it suitable for high-temperature precision filtration of edible vegetable oils.

[0009] According to one aspect of this application, a perfluoroethylene propylene hollow fiber microporous membrane for edible oil filtration is provided, which is prepared by comprising the following components by weight percentage: The polytetrafluoroethylene propylene resin is 63~72wt%, of which the molar content of hexafluoropropylene structural units is 11~14%; The water-soluble composite porogen is 22-29 wt%, which is prepared by wet compounding and graded drying of inorganic salt components and polymer dispersion components. Fluorine-modified polyimide microfibers, 2-5 wt%.

[0010] Specifically, perfluoroethylene propylene resin serves as the continuous film-forming phase of the membrane, providing the hollow fiber membrane with the foundation for heat resistance, oil resistance, and chemical stability, and providing a continuous polymer backbone for subsequent melt spinning and solid-phase stretching.

[0011] By limiting the molar content of hexafluoropropylene structural units in poly(perfluoroethylene propylene) resin to the range of 11-14%, it is beneficial to achieve an appropriate balance between the melt processing performance and the formation of the crystal structure of poly(perfluoroethylene propylene). This allows the resin to maintain a suitable melt processing state even when it contains a large amount of water-soluble composite pore-forming agent, and provides a stable material basis for subsequent cooling solidification and solid-phase stretching to form a microporous structure.

[0012] A water-soluble composite pore-forming agent, acting as a elutable second phase, is dispersed within the continuous poly(perfluoroethylene propylene) phase during melt blending. After stretching and subsequent washing, it is removed from the membrane, forming interconnected micropores within the membrane. Fluorinated modified polyimide microfibers, acting as a dispersing reinforcement phase, enhance the membrane's mechanical strength and deformation resistance through their fibrous structure. Furthermore, their fluorinated structure improves the interfacial affinity between the microfiber and the continuous poly(perfluoroethylene propylene) phase, allowing for more uniform dispersion within the matrix and regulating local deformation during subsequent stretching. These three components respectively fulfill the roles of continuous film formation, elutable pore formation, reinforcement, and interfacial deformation regulation, forming a synergistic material system. This allows for the creation of a bulk poly(perfluoroethylene propylene) microporous membrane with filtration capabilities without the need for an external polyimide separation coating.

[0013] Optionally, in the water-soluble composite pore-forming agent, the mass ratio of the inorganic salt component to the polymer dispersion component is (70~85):(15~30). Preferably, the mass ratio of the inorganic salt component to the polymer dispersion component is (75~82):(18~25).

[0014] By limiting the overall ratio of inorganic salt components to polymer dispersion components in the water-soluble composite pore-forming agent, the pore-forming dispersion effect and pore quality can be controlled. This ratio range allows the inorganic salt to provide sufficient porosity as the main pore-forming component, while the polymer dispersion components form an effective coating and dispersion network, avoiding local defects caused by direct exposure of salt particles.

[0015] When the inorganic salt content is too low, the effective content of the elutable pore-forming phase decreases, which is not conducive to the formation of a microporous structure with sufficient connectivity. When the polymer dispersion component content is too low, it may be difficult to effectively suppress the agglomeration of inorganic salt particles during wet compounding, drying, and subsequent melt blending processes, resulting in uneven local pore size and increasing the possibility of abnormal macropore formation. On the other hand, an excessively high polymer dispersion component content will increase the proportion of non-porous organic components, thereby reducing the proportion of the effective inorganic salt pore-forming phase and affecting the dispersion state of the water-soluble composite pore-forming agent in the polytetrafluoroethylene propylene melt.

[0016] Optionally, the inorganic salt component comprises two or three of sodium chloride, potassium chloride, and anhydrous calcium chloride; the polymer dispersion component is a compound of polyvinylpyrrolidone and sodium polyacrylate; and the particle size of the inorganic salt component is preferably D50 of 100–500 nm.

[0017] D50 particles are secondary particles at the processing scale, primarily used to improve the metering and conveying of the porous phase and the overall dispersion stability during melt blending. The inorganic salt component is equivalent to being dispersed as smaller primary particles within the composite pore-forming agent. After the composite pore-forming agent enters the polytetrafluoroethylene (PTFE) melt, it undergoes a certain degree of depolymerization and spatial redistribution during melt mixing and subsequent spinning, dispersing the inorganic salt primary particles or localized porous units composed of multiple primary particles within the polymer continuous phase. During subsequent stretching, interfacial debonding and localized cavitation occur between the polymer continuous phase and the inorganic salt porous phase. After water washing removes the water-soluble inorganic salt, an interconnected microporous structure is formed. Therefore, the final pore structure is jointly determined by the size of the inorganic salt primary particles, the dispersion state of the porous phase, the FEP solidification and crystallization structure, and the stretching cavitation behavior.

[0018] Preferably, the mass ratio of sodium chloride, potassium chloride, and anhydrous calcium chloride in the inorganic salt component is (25~35):(10~15):(10~18); and the mass ratio of polyvinylpyrrolidone to sodium polyacrylate in the polymer dispersion component is (6~10):(3~6).

[0019] Specifically, a combination of multiple inorganic salts utilizes their varying solubility and particle morphology to form multi-scale dissolution pores, broadening the effective filtration pore size window. Polyvinylpyrrolidone provides excellent film-forming and dispersing capabilities, while sodium polyacrylate enhances hydrophilicity and dissolution assistance; together, they synergistically inhibit recrystallization and agglomeration of the salts during the drying process. Under the aforementioned proportions, the water solubility and thermal stability of the composite pore-forming agent can be controlled, ensuring stable dispersion of the pore-forming agent during melt spinning and low residue after washing. This helps reduce the risk of residual soluble pore-forming components, while simultaneously optimizing pore connectivity and increasing hot oil flux.

[0020] Optionally, by weight percentage, it also contains 1-4 wt% polytetrafluoroethylene micropowder and 0.3-1.5 wt% hydrophobically modified nano-silica; The polytetrafluoroethylene micro powder has a particle size of 0.2~1.0μm, and the hydrophobically modified nano-silica has a particle size of 15~50nm.

[0021] Specifically, nano-silica with an average particle size of 15–50 nm is dispersed in anhydrous ethanol to prepare a 10 wt% dispersion; 5% methyltrimethoxysilane relative to the mass of nano-silica is added, and the mixture is stirred at 60 °C for 2–3 h; after the reaction is completed, the mixture is filtered or centrifuged, unreacted material is removed by washing with ethanol, and the mixture is dried at 100 °C to obtain hydrophobically modified nano-silica.

[0022] As a preferred approach, a limited proportion of polytetrafluoroethylene (PTFE) micropowder and hydrophobically modified nano-silica can be added to the original formula. PTFE micropowder, as a fluorine-based rigid dispersed phase, belongs to the same fluoropolymer system as the FEP matrix, exhibiting better interfacial compatibility than non-fluorine inorganic particles. During stretching, it can act as a stress concentration point to assist in cavitation and pore formation. Simultaneously, its high heat resistance can strengthen the pore wall structure and reduce the thermal shrinkage rate of the pores under high-temperature conditions. Hydrophobically modified nano-silica can refine the FEP grains, improve the uniformity of grain boundary distribution, thereby improving the uniformity of pore formation, while also reinforcing the creep resistance of the pore walls. The synergistic effect of these two components can simultaneously improve the pore quality and long-term thermal stability of the membrane.

[0023] Optionally, the fluorinated modified polyimide microfiber has a diameter of 0.5~2μm and an aspect ratio of 30~150.

[0024] Specifically, the fluorinated modified polyimide microfiber is a modified polyimide short fiber with fluorinated aliphatic groups introduced into its side chain, and is a commercially available organic reinforcing filler. The fluorinated aliphatic groups are selected from trifluoromethyl, fluorinated alkyl, or fluorinated alkoxy groups.

[0025] The microfibers within this size range are easily oriented and aligned during melt blending and spinning, forming an axially reinforcing skeleton that effectively transfers stress, significantly improving the axial tensile strength of the membrane. The aspect ratio ensures that the microfibers are fully entangled with the matrix without excessive aggregation, avoiding stress concentration points. In conjunction with subsequent differential cooling and staged stretching processes, the pore orientation and mechanical anisotropy balance can be further optimized, improving the structural integrity of the membrane under backwashing and hot oil impact.

[0026] Optionally, the membrane has a porosity of 40-55% and an axial tensile strength ≥65N; under conditions of a transmembrane pressure difference of 0.1 MPa and a temperature of 80℃, the steady-state flux using refined soybean oil as the filter medium is ≥90 L·m⁻¹. - ²·h - ¹.

[0027] Specifically, the hollow fiber microporous membrane has an outer diameter of 2.0–2.4 mm, an inner diameter of 1.0–1.2 mm, and an average wall thickness of 0.50–0.60 mm.

[0028] According to another aspect of this application, a method for preparing the polytetrafluoroethylene propylene hollow fiber microporous membrane as described above is also provided, comprising the following steps: (1) Preparation of water-soluble composite porogen: Polyvinylpyrrolidone and sodium polyacrylate are dissolved in water to prepare a polymer dispersion, inorganic salt components are added and mixed evenly, and then the water-soluble composite porogen particles are obtained by graded drying, crushing and sieving. Preferably, the D50 of the obtained composite porogen particles is 20–80 μm.

[0029] (2) Melt blending and granulation: After premixing polytetrafluoroethylene propylene resin, water-soluble composite pore-forming agent and fluorinated modified polyimide microfiber, the mixture is melt-blended, extruded, cooled and granulated by a twin-screw extruder to obtain spinning masterbatch; (3) Differential cooling melt spinning: The spinning masterbatch is melted and plasticized and then extruded through a hollow annular spinneret to form hollow nascent fibers. The solidification and crystallization structure is controlled by adjusting the difference in cooling conditions between the inner and outer sides of the fiber. (4) Staged solid-phase stretching: The cooled hollow nascent fibers are subjected to staged solid-phase stretching with a total stretching ratio of 2.2 to 3.5 times to form a microporous precursor structure; (5) Gradient water washing to remove pores: The water-soluble pore-forming components are removed by gradient heating water washing, followed by pure water countercurrent extraction and drying to obtain the nascent microporous membrane; (6) Fixed-length heat setting: High-temperature heat treatment is carried out under constant tension, and the polytetrafluoroethylene hollow fiber microporous membrane is obtained after cooling.

[0030] Optionally, in step (1), polyvinylpyrrolidone and sodium polyacrylate are first added to deionized water and stirred at 40-70°C until completely dissolved, and then the inorganic salt component is added for dispersion. The graded drying process involves first vacuum low-temperature concentration to a solid content of 45-60 wt%, followed by gradient temperature drying to a moisture content ≤1.0 wt%. Preferably, after drying, the product is aged at a low temperature of 60-75℃ for 1-3 hours before being crushed and screened.

[0031] Specifically, vacuum concentration involves placing the composite porous slurry under reduced pressure at 45–60°C, with the vacuum level controlled at -0.06 to -0.09 MPa. During the concentration process, the mixture is continuously and slowly stirred to ensure uniform evaporation of water from the system. Concentration is stopped when the solid content of the slurry reaches 45–60 wt%.

[0032] The gradient temperature drying process is divided into two atmospheric pressure stages: the first stage is drying at 50-60℃ for 2-4 hours, with continuous and slow water loss to prevent salt particles from rapidly migrating and agglomerating with the moisture; the second stage is drying at 70-85℃ for 4-8 hours to further remove bound water and residual moisture.

[0033] Furthermore, for embodiments that require further improvement in the thermal stability and pore uniformity of the membrane, in step (2), polytetrafluoroethylene micro powder and hydrophobically modified nano-silica may be added during premixing; premixing is carried out at room temperature for 5 to 10 minutes to ensure uniform mixing of all components and obtain a premixed material, which is then added to a twin-screw extruder for melt blending.

[0034] Optionally, in step (2), the twin-screw extruder is set with three temperature gradients along the direction from feed to die head: feed section 240~260℃, melting section 255~275℃, homogenization section 270~285℃; spinning temperature 275~285℃; screw speed 50~150rpm, and material residence time in barrel 2~8min; the twin-screw extruder adopts a temperature gradient that gradually increases from feed section, melting section to homogenization section, which is conducive to the material completing controlled plasticization, full melting and uniform mixing in sequence, while avoiding premature local migration or dispersion instability of composite pore-forming agent at excessively high temperature.

[0035] In step (3), dry gas at a temperature of 80~180℃ is introduced into the inner side of the fiber to achieve slow cooling, while the outer side of the fiber is cooled rapidly by a gradient cooling air bath at a temperature of 30~150℃; the temperature of the inner cooling medium is 30~100℃ higher than the temperature of the outer air bath. In step (4), the staged solid-state stretching includes: a first stage of preheating and pre-orientation stretching at a temperature of 80-120℃ with a stretching ratio of 1.1-1.3 times; an intermediate stress adjustment stage at a temperature of 100-150℃ with a dwell time of 3-15s; and a second stage of medium-temperature main stretching at a temperature of 140-190℃ with a stretching ratio of 1.5-2.5 times. The total stretching ratio is the product of the actual stretching ratios of each stage.

[0036] The solid-state stretching process employs a three-stage approach: preheating and pre-orientation stretching in the first stage, intermediate stress adjustment, and medium-temperature main stretching in the second stage. The first stage, low-ratio preheating and stretching, gradually establishes molecular chains and crystal region orientation, reducing stress concentration caused by a single high-ratio stretching. Intermediate stress adjustment helps mitigate the macroscopic residual stress formed in the previous stage. The second stage, main stretching, further promotes the formation of the microporous precursor structure of the membrane. This three-stage continuous process, combined with the composite pore-forming agent and the initial structure formed by differential cooling, enhances the stability of the pore-forming process and the mechanical integrity of the membrane fibers.

[0037] Optionally, in step (5), the gradient temperature water washing is performed as follows: constant temperature water washing at 40~60℃ for 2~4 h, constant temperature water washing at 70~90℃ for 4~10 h, and pure water countercurrent extraction at 90~100℃ for 6~16 h; after water washing, the product is dried with hot air at 80~100℃ to constant weight. In step (6), the control tension for fixed-length heat setting is 0.3~1.0 cN / dtex, the heat treatment temperature is 210~260℃, and the treatment time is 10~40 min; after the treatment is completed, it is slowly cooled to room temperature.

[0038] The beneficial effects of this application include, but are not limited to: 1. This application adopts a bulk pore-forming route, which can achieve effective filtration without the need for an external polyimide separation coating. This solves the problem of the lifespan of external coatings, which are prone to swelling and peeling in high-temperature non-polar oils. At the same time, it avoids the residual risks of toxic organic solvents and crosslinking agents during the coating preparation process, and significantly improves food contact safety and long-term working stability.

[0039] 2. This application uses a water-soluble composite pore-forming agent instead of a single pore-forming component. Through the composite design of inorganic salt components and polymer dispersion components, the inorganic salt not only undertakes the main pore-forming function, but also achieves a relatively uniform dispersion state under the adjustment of the polymer dispersion component. Compared with the problem of local agglomeration easily caused by single inorganic salts, this composite pore-forming system is beneficial to reducing the local abnormal pore structure caused by large particle agglomeration, and makes the subsequent melt blending, solid-phase stretching, and water washing depore removal processes more seamless.

[0040] 3. In the preparation method of this application, the radial crystallization gradient is controlled by differential cooling inside and outside, and the crystallization difference is converted into pore size difference by staged stretching. The rapid solidification on the outside is conducive to surface densification, while the slow cooling on the inside promotes the development of the internal pore precursor structure. The dense layer on the outside ensures the retention accuracy, while the loose layer on the inside reduces the mass transfer resistance. A good balance is achieved between filtration accuracy and edible oil flow resistance without relying on the coating layer.

[0041] 4. The preparation method of this application is optimized for high-temperature filtration of edible oil, from matrix crystallization control and pore wall reinforcement to fixed-length heat setting. The membrane has high mechanical strength and good fatigue resistance, is suitable for repeated backwashing and cleaning in industrial conditions, has low performance degradation under long-term high-temperature oil filtration conditions, and the process is green and environmentally friendly, and is easy to scale up industrially. Attached Figure Description

[0042] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a process flow diagram illustrating the preparation of the poly(perfluoroethylene propylene) hollow fiber microporous membrane according to an embodiment of this application. Figure 2 The images are scanning electron microscope (SEM) images of the polytetrafluoroethylene propylene hollow fiber microporous membrane of Example 1 of this application; wherein (a) is the low magnification morphology of the cross-section of the hollow fiber membrane, (b) is the microstructure of the outer layer of the membrane wall, (c) is the microstructure of the middle layer of the membrane wall, (d) is the microstructure of the inner layer of the membrane wall, and (e) is the morphology of the outer surface of the membrane fibers. Detailed Implementation

[0043] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described in this patent are for illustrative purposes only.

[0045] The main raw materials used in this invention are all commercially available conventional industrial-grade or analytical-grade products, with specific specifications as follows: Perfluoroethylene propylene (FEP) resin: FEP-1: 12.5% ​​molar content of hexafluoropropylene (HFP) structural units, melt index 5.2 g / 10min (372℃, 5kg), used as the base raw material for the examples; FEP-2: 8.0% molar content of hexafluoropropylene (HFP) structural units, melt index 2.4 g / 10min (372℃, 5kg), used for comparative example 1. Inorganic salt raw materials: sodium chloride, potassium chloride, anhydrous calcium chloride, analytical grade, initial particle size D 50 The wavelength is 200–300 nm. Water-soluble polymer: Polyvinylpyrrolidone (PVP): K60 type, weight-average molecular weight approximately 4.0 × 10⁻⁶. 5 Sodium polyacrylate (PAAS): 90% neutralization, weight-average molecular weight approximately 5.0 × 10³. Fluorinated modified polyimide microfibers: fiber diameter 1.0 μm, aspect ratio 100. Polytetrafluoroethylene (PTFE) micropowder: low molecular weight suspension grade, particle size 0.5 μm. Hydrophobically modified nano-silica: particle size 30 nm.

[0046] Filter media: Grade I refined soybean oil (kinematic viscosity at 80℃ is about 22 mm² / s, used for flux testing); unrefined rapeseed oil (initial turbidity is about 120 NTU, used for retention performance testing).

[0047] Main experimental equipment: twin-screw extruder (SHJ-20 type), hollow fiber melt spinning test machine (including hollow annular spinneret).

[0048] Example 1 Formulation composition: Based on a total mass of 100 parts, it contains 72 parts FEP-1 resin, 23 parts water-soluble composite porogen, and 5 parts fluorinated modified polyimide microfiber. Within the water-soluble composite porogen: the mass ratio of inorganic salt components to polymer dispersion components is 80:20; the mass ratio of sodium chloride, potassium chloride, and anhydrous calcium chloride in the inorganic salts is 30:12:15; and the mass ratio of PVP to PAAS in the polymer dispersion components is 8:5.

[0049] Preparation steps: (1) Preparation of water-soluble composite porogen: PVP was added to deionized water according to the ratio and stirred at 60°C for 30 min until completely dissolved; PAAS was slowly added and stirred for 40 min to obtain a uniform polymer dispersion; anhydrous calcium chloride was added to the dispersion and stirred at 50°C and 500 rpm for 25 min; potassium chloride was added and stirred at the same temperature for 25 min; sodium chloride was added and dispersed at 1200 rpm for 20 min to obtain a multi-salt composite suspension system; the suspension system was placed under vacuum at 50°C and -0.08 MPa to be slowly concentrated to a solid content of about 55 wt% and allowed to stand for 60 min; then gradient drying was carried out: first dried at 55°C under normal pressure for 3 h, then heated to 80°C and dried for 6 h, and the final water content was measured to be 0.72 wt%; after drying, it was aged at 70°C for 2 h, and after natural cooling, it was crushed by low shear jaw crusher and passed through a 120-mesh standard inspection sieve to obtain composite porogen particles with a D50 of about 45 μm.

[0050] (2) Melt blending and granulation: After the FEP-1 resin is vacuum dried at 100℃ for 6 hours, it is added to a high-speed mixer along with the composite pore-forming agent and fluorine-modified polyimide microfibers. The mixture is mixed at room temperature for 8 minutes until it is evenly dispersed. The mixture is added to a twin-screw extruder, and three temperature gradients are set along the feed to the die head: 280℃ for the feed section, 305℃ for the melting section, and 320℃ for the homogenization section. The screw speed is 100 rpm, and the material residence time is about 5 minutes. The extruded strip is cooled by water and granulated to obtain spinning masterbatch.

[0051] (3) Differential cooling melt spinning: The spinning masterbatch is melted and plasticized by a single screw extruder, with temperatures of 250℃, 260℃ and 280℃ in each section; the metering pump delivers the masterbatch quantitatively to the hollow annular spinneret, with a spinneret temperature of 280℃ and a spinning draw ratio of 1.4; dry nitrogen gas at 120℃ is introduced into the inner side of the fiber to maintain the hollow structure and achieve slow cooling of the inner wall; the outer side of the fiber is rapidly cooled by a gradient cooling air bath with a length of 50cm, with an inlet temperature of 120℃, an outlet temperature of 40℃ and a wind speed of 0.5m / s; the average temperature difference between the inner and outer cooling media is about 60℃.

[0052] (4) Staged solid phase stretching: The collected nascent fibers are continuously stretched offline with a total stretching ratio of 3.0 times; the first stage is preheating and pre-orientation stretching: temperature 100℃, stretching ratio 1.2 times; intermediate stress adjustment section: temperature 120℃, dwell time 8s; the second stage is medium temperature main stretching: temperature 170℃, stretching ratio 2.5 times; after stretching, it is immediately air-cooled for shaping.

[0053] (5) Gradient water washing and depore removal: The stretched membrane fibers were washed in three stages: the first stage was a constant temperature water wash at 50℃ for 3 hours; the second stage was a constant temperature water wash at 80℃ for 7 hours; the third stage was a pure water countercurrent extraction at 95℃ for 12 hours; after the water washing was completed, the membrane fibers were dried at 90℃ with hot air to constant weight to obtain the nascent microporous membrane. (6) Fixed-length heat setting: The nascent microporous membrane is placed in a 240℃ hot air oven with a fixed-length tension of 0.6cN / dtex for 25min; after the treatment, it is slowly cooled to room temperature at a rate of 2℃ / min to obtain the final finished membrane.

[0054] Figure 2 This is a scanning electron microscope (SEM) image of the poly(perfluoroethylene propylene) hollow fiber microporous membrane from Example 1 of this application. Figure 2 As can be seen, the prepared polytetrafluoroethylene hollow fiber microporous membrane exhibits a regular hollow ring structure with uniform wall thickness distribution and no obvious macroscopic defects. The membrane wall as a whole displays a gradient pore structure with progressively increasing pore size from the outside to the inside: the outer layer of the membrane wall has fine pores and small pore size, serving as a functional layer for precision filtration and ensuring high retention accuracy; the middle and inner layers of the membrane wall have progressively larger pore sizes, forming a continuous and interconnected three-dimensional pore network, which can effectively reduce mass transfer resistance and significantly improve the membrane's permeate flux. The pore distribution on the outer surface of the membrane fibers is uniform, without macroporous defects or particle agglomeration, and the surface morphology is highly uniform.

[0055] Example 2 Except for the following adjustments to the formulation: 67.5 parts of FEP-1 resin, 28.5 parts of water-soluble composite porogen, and 4 parts of fluorine-modified polyimide microfiber, the specifications of the other raw materials, preparation steps, and process parameters in this embodiment are exactly the same as in Example 1.

[0056] Example 3 Except for the following adjustments to the formulation: 69 parts FEP-1 resin, 29 parts water-soluble composite porogen, and 2 parts fluorine-modified polyimide microfiber, the specifications of the other raw materials, preparation steps, and process parameters in this embodiment are exactly the same as in Example 1.

[0057] Example 4 In this embodiment, the formulation composition is adjusted to include: 64.5 parts of FEP-1 resin, 28.5 parts of water-soluble composite pore-forming agent, 4 parts of fluorine-modified polyimide microfiber, 2 parts of PTFE micro powder, and 1 part of hydrophobic modified nano silica. In the melt blending stage, PTFE micro powder and nano silica are added together with the main material for premixing. All other preparation steps and process parameters are exactly the same as in Example 1.

[0058] Example 5 Except for the following adjustments to the formulation: 66 parts FEP-1 resin, 28.5 parts water-soluble composite porogen, 4 parts fluorine-modified polyimide microfiber, 1 part PTFE micro powder, and 0.5 parts hydrophobic modified nano silica, the preparation steps and process parameters in this embodiment are exactly the same as in Example 4.

[0059] Example 6 Except for adjusting the mass ratio of inorganic salt component to polymer dispersion component in the water-soluble composite porogen to 90:10, the overall formulation, preparation steps and process parameters in this embodiment are exactly the same as in Example 2.

[0060] Example 7 Except for the fact that the water-soluble composite porogen contains only sodium chloride and PVP in a mass ratio of 80:20 and does not contain potassium chloride, anhydrous calcium chloride, or sodium polyacrylate, the overall formulation, preparation steps, and process parameters in this embodiment are exactly the same as in Example 2.

[0061] Comparative Example 1 In this comparative example, FEP-2 resin with an HFP molar content of 8.0% was used to replace FEP-1. The rest of the overall formulation, preparation steps and process parameters were exactly the same as in Example 2.

[0062] Comparative Example 2 In this comparative example, sodium chloride, potassium chloride, calcium chloride, PVP, and PAAS were directly added to a high-speed mixer and mixed for 10 minutes according to the proportions in Example 2. The mixture was then ball-milled to a D50 of approximately 45 μm without wet dispersion, concentration, or gradient drying. All other overall formulations, subsequent preparation steps, and process parameters were exactly the same as in Example 2.

[0063] Comparative Example 3 In this comparative example, the fluorine-modified polyimide microfibers were removed, and the reduced mass was made up by FEP-1 resin, i.e., 71.5 parts of FEP-1 resin and 28.5 parts of water-soluble composite porogen; the remaining preparation steps and process parameters were exactly the same as in Example 2.

[0064] Comparative Example 4 In this comparative example, the fibers were uniformly cooled by air at 25°C on both the inner and outer sides during the spinning process, and the rest of the formulation and preparation steps were exactly the same as in Example 2.

[0065] Comparative Example 5 This comparative example uses a single-stage stretching method, directly stretching the nascent fibers to a total ratio of 3.0 times at 170°C in one go, without a preheating and pre-orientation section or an intermediate stress adjustment section; the rest of the formulation and preparation steps are exactly the same as in Example 2.

[0066] Experimental Example 1. Testing methods and reference standards All samples were tested using a standardized method, with at least three parallel tests performed. The arithmetic mean was taken as the final result. Performance tests were conducted according to the following standards: (1) Porosity test: The n-butanol displacement method was used. The membrane fibers dried to constant weight were weighed and recorded as m0. They were then immersed in n-butanol and degassed under vacuum for 30 min until fully wetted. After removing the membrane fibers and wiping off the surface liquid, they were weighed and recorded as m1. The porosity was measured according to the formula ε=(m1-m0) / (ρ正丁醇 The porosity is calculated as V)×100%, where V is the total geometric volume of the membrane filaments.

[0067] (2) Axial breaking strength test: Adjusted according to GB / T 14344-2008 "Test Method for Tensile Properties of Chemical Fiber Filaments", a universal testing machine was used with a gauge length of 100 mm and a tensile rate of 50 mm / min; the finished membrane filament specifications were: outer diameter 2.2 mm, inner diameter 1.1 mm, and wall thickness approximately 0.55 mm. The maximum breaking load of a single membrane filament was tested at room temperature. Ten parallel samples were tested in each group, and the arithmetic mean was taken.

[0068] (3) Steady-state oil flux test: Refer to the flux test method in HY / T112-2008 "Test Methods for Ultrafiltration Membranes and Their Components", adopt a laboratory cross-flow filtration device, use refined soybean oil as the filter medium, fill the membrane module with membrane fibers with an effective length of 30cm, and calculate the effective filtration area based on the outer surface of the membrane fibers; keep the system at a constant temperature of 80℃, stabilize the transmembrane pressure difference at 0.1MPa, and run continuously until the flux fluctuation is ≤5% in 3 consecutive samplings, which is judged as steady state, and record the steady-state flux value.

[0069] (4) Turbidity removal rate test: Referring to the turbidity determination method in GB / T5750.4-2006 "Standard Examination Methods for Drinking Water: Sensory Characteristics and Physical Indicators", unrefined rapeseed oil was used as the feed liquid. After stable filtration for 30 minutes at 80℃ and 0.1MPa, the turbidity of the feed liquid and the permeate were tested respectively. The turbidity removal rate was calculated according to the formula R=(T0-T1) / T0×100%, where T0 is the turbidity of the feed liquid and T1 is the turbidity of the permeate.

[0070] (5) Dry heat shrinkage rate test: Adjust according to GB / T6505-2008 "Test method for heat shrinkage rate of chemical fiber filament", take a film filament with an initial length of 500mm, hang it at both ends at a fixed length in a 100℃ hot air oven for 168h, take it out and cool it to room temperature and measure the length; calculate the axial heat shrinkage rate according to the formula S=(L0-L1) / L0×100%.

[0071] (6) Flux recovery rate test: Refer to the anti-fouling performance evaluation method in HY / T112-2008. After completing the initial flux test, backwash with 80℃ pure water at a pressure of 0.15MPa for 10 minutes. Repeat the "filtration-cleaning" cycle 5 times and then test the steady-state flux again. Calculate the flux recovery rate according to the formula FRR=F1 / F0×100%, where F0 is the initial flux and F1 is the flux after 5 cleaning cycles.

[0072] 2. Experimental Results and Data The core performance test results of each embodiment and comparative example are shown in Table 1 below: Table 1

[0073] In summary, the polytetrafluoroethylene propylene hollow fiber microporous membranes prepared using the formulation and process specified in this application exhibit stable and balanced porosity, tensile strength, oil flux, and turbidity removal rate within the specified ranges. In Examples 1-5, the porosity is consistently between 45% and 49%, the axial tensile strength is higher than 65 N, and the steady-state soybean oil flux at 80°C is higher than 90 L. m - ² h - ¹, the turbidity removal rate is higher than 91%, the overall performance is balanced and stable, and it can stably achieve excellent mechanical strength while also having good permeation flux and retention accuracy.

[0074] Comparative Example 1 used FEP resin with an HFP molar content of 8.0%, which is lower than the range specified in this application. Its steady-state flux decreased by 30.8% and porosity decreased by 7.4 percentage points compared to Example 2. The reason for this is that too low an HFP content leads to excessively high crystallinity of FEP, resulting in overly dense crystalline regions. This makes it difficult to form effective cavitation and interconnected channels during stretching, ultimately leading to a decline in permeability. Comparative Example 2 used a dry powder direct mixing process to prepare a pore-forming agent. Its turbidity removal rate decreased by 7.8 percentage points and steady-state flux decreased by 26.0% compared to Example 2. This is because dry powder mixing cannot achieve effective coating of salt particles by the polymer. During high-temperature melt blending, salt particles are prone to agglomeration, forming defective macropores. At the same time, the interfacial bonding force between the two phases is insufficient, ultimately leading to a simultaneous deterioration in filtration accuracy and flux.

[0075] In Comparative Example 3, after removing the fluorinated modified polyimide microfibers, the axial breaking strength decreased by 15.9% compared to Example 2, while the dry heat shrinkage rate increased by 0.29 percentage points. This is attributed to the microfibers forming a reinforcing network along the axial direction, improving mechanical and thermal dimensional stability, and also enhancing pore connectivity through interfacial cavitation. In Comparative Example 4, the differential cooling was eliminated, and uniform room temperature cooling was used. The turbidity removal rate decreased by 3.9 percentage points compared to Example 2, and the steady-state flux decreased by 18.3%. This is because a homogeneous pore structure cannot simultaneously achieve both retention accuracy and mass transfer efficiency. In Comparative Example 5, a single-stage, one-time stretching method was used. The axial breaking strength decreased by 20.3% compared to Example 2, while the dry heat shrinkage rate increased by 0.36 percentage points. During single-stage stretching, internal stress cannot be released stepwise, easily causing internal fiber damage and uneven pore distribution.

[0076] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A perfluoroethylene propylene hollow fiber microporous membrane for edible oil filtration, characterized in that, It is prepared by comprising the following components by weight percentage: The polytetrafluoroethylene propylene resin is 63~72wt%, of which the molar content of hexafluoropropylene structural units is 11~14%; The water-soluble composite porogen is 22-29 wt%, which is prepared by wet compounding and graded drying of inorganic salt components and polymer dispersion components. Fluorine-modified polyimide microfibers, 2-5 wt%.

2. The polytetrafluoroethylene propylene hollow fiber microporous membrane according to claim 1, characterized in that, In the water-soluble composite pore-forming agent, the mass ratio of the inorganic salt component to the polymer dispersion component is (70~85):(15~30). Preferably, the mass ratio of the inorganic salt component to the polymer dispersion component is (75~82):(18~25).

3. The polytetrafluoroethylene propylene hollow fiber microporous membrane according to claim 2, characterized in that, The inorganic salt component comprises two or three of sodium chloride, potassium chloride, and anhydrous calcium chloride; the polymer dispersion component is a compound of polyvinylpyrrolidone and sodium polyacrylate. Preferably, the mass ratio of sodium chloride, potassium chloride, and anhydrous calcium chloride in the inorganic salt component is (25~35):(10~15):(10~18); and the mass ratio of polyvinylpyrrolidone to sodium polyacrylate in the polymer dispersion component is (6~10):(3~6).

4. The polytetrafluoroethylene propylene hollow fiber microporous membrane according to claim 1, characterized in that, By weight percentage, it also contains 1-4 wt% polytetrafluoroethylene micropowder and 0.3-1.5 wt% hydrophobically modified nano-silica; The polytetrafluoroethylene micro powder has a particle size of 0.2~1.0μm, and the hydrophobically modified nano-silica has a particle size of 15~50nm.

5. The polytetrafluoroethylene propylene hollow fiber microporous membrane according to claim 1, characterized in that, The fluorinated modified polyimide microfibers have a diameter of 0.5~2μm and an aspect ratio of 30~150.

6. The polytetrafluoroethylene propylene hollow fiber microporous membrane according to claim 1, characterized in that, The membrane has a porosity of 40–55% and an axial tensile strength ≥65 N; under conditions of a transmembrane pressure difference of 0.1 MPa and a temperature of 80 °C, the steady-state flux using refined soybean oil as the filter medium is ≥90 L·m⁻¹. - ²·h - ¹.

7. A method for preparing a polytetrafluoroethylene propylene hollow fiber microporous membrane as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Preparation of water-soluble composite porogen: Polyvinylpyrrolidone and sodium polyacrylate are dissolved in water to prepare a polymer dispersion, inorganic salt components are added and mixed evenly, and then the water-soluble composite porogen particles are obtained by graded drying, crushing and sieving. (2) Melt blending and granulation: After premixing polytetrafluoroethylene propylene resin, water-soluble composite pore-forming agent and fluorinated modified polyimide microfiber, the mixture is melt-blended, extruded, cooled and granulated by a twin-screw extruder to obtain spinning masterbatch; (3) Differential cooling melt spinning: The spinning masterbatch is melted and plasticized and then extruded through a hollow annular spinneret to form hollow nascent fibers. The solidification and crystallization structure is controlled by adjusting the difference in cooling conditions between the inner and outer sides of the fiber. (4) Staged solid-phase stretching: The cooled hollow nascent fibers are subjected to staged solid-phase stretching with a total stretching ratio of 2.2 to 3.5 times to form a microporous precursor structure; (5) Gradient water washing to remove pores: The water-soluble pore-forming components are removed by gradient heating water washing, followed by pure water countercurrent extraction and drying to obtain the nascent microporous membrane; (6) Fixed-length heat setting: High-temperature heat treatment is carried out under constant tension, and the polytetrafluoroethylene hollow fiber microporous membrane is obtained after cooling.

8. The preparation method according to claim 7, characterized in that, In step (1), polyvinylpyrrolidone and sodium polyacrylate are first added to deionized water and stirred at 40-70°C until completely dissolved, and then the inorganic salt component is added for dispersion. The graded drying process involves first vacuum low-temperature concentration to a solid content of 45-60 wt%, followed by gradient temperature drying to a moisture content ≤1.0 wt%. Preferably, after drying, the product is aged at a low temperature of 60-75℃ for 1-3 hours before being crushed and screened.

9. The preparation method according to claim 7, characterized in that, In step (2), the twin-screw extruder is set with three temperature gradients along the direction from feed to die head: feed section 240~260℃, melting section 255~275℃, homogenization section 270~285℃; screw speed is 50~150 rpm, and material residence time in the barrel is 2~8 min; In step (3), dry gas at a temperature of 80~180℃ is introduced into the inner side of the fiber to achieve slow cooling, while the outer side of the fiber is cooled rapidly by a gradient cooling air bath at a temperature of 30~150℃; the temperature of the inner cooling medium is 30~100℃ higher than the temperature of the outer air bath. In step (4), the phased solid-phase stretching includes: the first stage of preheating and pre-orientation stretching, with a temperature of 80~120℃ and a stretching ratio of 1.1~1.3 times; the intermediate stress adjustment section, with a temperature of 100~150℃ and a dwell time of 3~15s; and the second stage of medium-temperature main stretching, with a temperature of 140~190℃ and a stretching ratio of 1.5~2.5 times.

10. The preparation method according to claim 7, characterized in that, In step (5), the gradient temperature water washing is as follows: constant temperature water washing at 40~60℃ for 2~4 h, constant temperature water washing at 70~90℃ for 4~10 h, and pure water countercurrent extraction at 90~100℃ for 6~16 h; after water washing, it is dried with hot air at 80~100℃ to constant weight. In step (6), the control tension for fixed-length heat setting is 0.3~1.0 cN / dtex, the heat treatment temperature is 210~260℃, and the treatment time is 10~40 min; after the treatment is completed, it is slowly cooled to room temperature.

Citation Information

Patent Citations

  • Polyperfluorovinyl hollow fiber membrane

    CN115337796A